Perencanaan Strategis Kawasan Berbasis Tata Kelola Lingkungan Terdesentralisasi yang Baik pada Kawasan Situ Gede Kota Tasikmalaya - Setiawan, Tomi (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2019)
This paper aims to explain the lake strategic planning of Situ Gede in Tasikmalaya municipality based on good decentralized environmental governance. This study used qualitative methods with research techniques consisting of non-participatory observation, interview, literature study and documentation. Then the data are analyzed through a three-stage model of data analysis namely data reduction, data display, and conclusions and verification. The result of the research indicates that the Situ Gede area strategic planning which supports good decentralized environmental governance is participatory, where the community is included in each stage of planning, so they have a sense of ownership and a sense of responsibility as a guarantee of the sustainability of the program's implementation. In every stage of planning up to the implementation it must involve the whole community so that the community can learn and feel the benefits of each stage directly. Then, at each stage it must be done collaboratively with the involvement of all relevant stakeholders to avoid conflicts of interest between sectors.